Calcium phosphate substrates with emulsion-derived roughness: Processing, characterisation and interaction with human mesenchymal stem cells. Issue 3 (March 2018) - Costa Machado, Gil; García-Tuñón, Esther; Bell, Robert V.; Alini, Mauro; Saiz, Eduardo; Peroglio, Marianna
Abstract: Calcium phosphates (CaP) have been the subject of several studies that often lack a systematic approach to understanding how their properties affect biological response. CaP particles functionalised with a pH-responsive polymer (BCS) were used to prepare microporous substrates (porosity between 70 and 75% and pore sizes of 5–20 μm) through the aggregation of oil-in-water emulsions by controlling solid loading, emulsification energy, pH, drying and sintering conditions. The combined effect of surface roughness (roughness amplitude, Ra between 0.9–1.7 μm) and chemistry (varying Hydroxyapatite/β-Tricalcium phosphate ratio) on human mesenchymal stem cells was evaluated. HA substrates stimulated higher cell adhesion and proliferation (especially with lower Ra ), but cell area increased with β-TCP content. The effect of surface roughness depended of chemistry: HA promoted higher mineralising activity when Ra  ∼ 1.5 μm, whereas β-TCP substrates stimulated a more osteogenic profile when Ra  ∼ 1.7 μm. A novel templating method to fabricate microporous CaP substrates was developed, opening possibilities for bone substitutes with controlled features.